2015
DOI: 10.1186/s12913-015-0896-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward inter-hospital electronic patient record exchange: discrepancies among physicians, medical record staff, and patients

Abstract: BackgroundIn this era of ubiquitous information, patient record exchange among hospitals still has technological and individual barriers including resistance to information sharing. Most research on user attitudes has been limited to one type of user or aspect. Because few analyses of attitudes toward electronic patient records (EPRs) have been conducted, understanding the attitudes among different users in multiple aspects is crucial to user acceptance. This proof-of-concept study investigated the attitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…Analysis revealed that physician and medical care satisfaction were positively correlated with sense of protected confidentiality, while physician dissatisfaction was negatively correlated with sense of protected confidentiality. In line with this latter finding, confidentiality concerns were positively correlated with that of patients [20]. This current study found that most patients are comfortable with computer use on the inpatient psychiatric unit as it is used in patient care.…”
Section: Discussionsupporting
confidence: 83%
“…Analysis revealed that physician and medical care satisfaction were positively correlated with sense of protected confidentiality, while physician dissatisfaction was negatively correlated with sense of protected confidentiality. In line with this latter finding, confidentiality concerns were positively correlated with that of patients [20]. This current study found that most patients are comfortable with computer use on the inpatient psychiatric unit as it is used in patient care.…”
Section: Discussionsupporting
confidence: 83%
“…The sooner this can happen, the more reasonable it is to move the health system towards computer-only information systems. Perceived usefulness has emerged in the broader literature as an important determinant of EHIS success [25]. …”
Section: Discussionmentioning
confidence: 99%
“…• Security and privacy: due to security and privacy concerns [44][45][46], many physicians and healthcare providers prefer to store patient records on computers or local systems that are not connected to the Internet [47]. Despite the benefits of large-scale HIE, a comparative study of the medical record exchange practices in Australia, Canada Germany, Netherlands, New Zealand, the UK and the US [48] revealed that Germany lacks a single approach for HIE and that healthcare software companies have achieved minimal success in their development of infrastructures where physicians can exchange clinical data due to security concerns.…”
Section: Healthcare System Challengesmentioning
confidence: 99%